The Impact of Moral Sensitivity, Transparency, and Community Participation on the Achievement of Village Sustainable Development Goals (SDGs) - Adelia Putri Nur Silviana; Dyah Ratnawati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
An essential aspect of the government's efforts to enhance community well-being across social, economic, and environmental areas is the sustainable development of villages. To fulfill this aim, the government established the Village Sustainable Development Goals (SDGs), promoting a development process that is more inclusive, engaging, and oriented towards the long term. Achieving these goals necessitates assistance from various sources, including active community participation in all stages of development, accountability in village leadership, and the ethical awareness of local officials. However, these targets have not been completely met in practice, especially concerning the Village Sustainable Development Goals (SDGs), as indicated by the existing disparities in village development measures. The main goal of this project is to explore and illustrate how moral awareness, transparency, and community involvement influence the attainment of Village Sustainable Development Goals (SDGs). Utilizing the Partial Least Squares Structural Equation Modeling technique, this quantitative study examines data obtained from community surveys. The findings reveal that the likelihood of achieving Village SDGs significantly increases with community participation, transparency, and ethical awareness. These results suggest that the moral sensitivity of village leaders and the engagement of the community contribute significantly to the successful accomplishment of Village Sustainable Development Goals (SDGs). This research enriches the available literature by broadening understanding, particularly in the fields of public sector accounting and village governance, about the factors that influence the effectiveness of Village SDGs through the integration of ethical governance, administrative procedures, and community participation. Furthermore, this study carries implications for policy, as the findings may be utilized by village administrations in developing policies that enhance governance in villages to maximize the realization of Village SDGs.